Changes in the structure and mechanical properties of bone tissues obtained from experimental animal models of lifestyle-related diseases / Ei Yamamoto and Yuki Kawamura - Ei, Yamamoto; Yuki, Kawamura (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Lifestyle-related diseases such as diabetes and hypertension are a major public health problem in the world. It is well known that these diseases directly affect the characteristics of cardiovascular tissues. However, there has been little information on the effects of diabetes or hypertension on the biomechanical properties of musculoskeletal tissues. We hypothesized that diabetes or hypertension is related to impaired material and structural properties of bones. To examine this hypothesis, mechanical loading tests were conducted to determine the stress-strain relations of cortical bone specimens obtained from experimental animal models of diabetes or hypertension. Zucker diabetic fatty rats (Diabetic group), stroke-prone spontaneously hypertensive rats (Hypertensive group), and normal Wistar rats (Control group) were used for the experiments. Cortical bone specimens were obtained from the femora of the rats, and compressive forces were applied to the specimens until failure using a conventional material tester. In addition, the trabecular structure of the femoral neck was observed using an X-ray micro-computed tomography. Bone compressive strength in the diabetic group was significantly lower than that of the control group. Trabecular bone in the hypertensive group has a higher porosity than that in the control group. These findings support the concept that bone metabolism may be impaired in diabetic or hypertensive subjects.